(untitled) (International Congress on Economics, Management and Business Studies, 2026)
The Vedas (from the Sanskrit veda meaning “knowledge” or “sacred knowledge”) constitute the oldest written and cultural monuments of Indian civilization. Their formation dates to the late second millennium BCE and the early first millennium BCE. As a corpus, the Vedas represent a fundamental source for understanding the religious beliefs, mythological concepts, social structures, and philosophical thought of ancient Indian society.